Disciples of Pasteur from Russia — 2 - Maxim M. Karapats; Lyudmila A. Kraeva (Инфекция и иммунитет, 2023)
In 2022, a global scientific community noted the 200th anniversary of the outstanding scientist, one of founders of a science of microbiology Louis Pasteur. Pasteurs works promoted formation of the microbic theory and gave a momentum to a search of ways for prevention of infections, including hospital ones. Among Pasteurs disciples and colleagues are E. Ru, I.I. Mechnikov as well as many Russian scientists. Not all family names of Pasteurs disciples were revealed to a wide range of readers. Much of them returned home and to bring a marked contribution to development of microbiology and immunology in Russia. Here, we continue seek out and return biographies of the Russian scientists Louis Pasteurs disciples. Among Russian scientists who passed school of Pasteur Institute there may be mentioned many graduates of one of the oldest medical institutions of Russia Military Medical academy as well as associates of I.I. Mechnikov and N.F. Gamalei J.J. Bardach, S.I. Zlatogorov, N.I. Chistovich, L.A. Tarasevich; renowned surgeons V.A. Ratimov and V.A. Oppel, one of founders of Pasteur Institute in Saint Petersburg P.P. Maslakovets. Many Pasteurs followers took part in creating the institute resembling Pasteur Institute nowadays known as the Institute of Experimental Medicine. In the latter regard, we mention E.F. Shperk, V.I. Nedrigajlov, etc. Moreover, it is also necessary to note the first woman in Russia Doctor P.V. Tsiklinskuju who was awarded a title Professor of Bacteriology. Pasteurs disciples received theoretical and practical knowledge from their teacher and returned to own Fatherlands to fully serve with full dedication. They brought with new methods of scientific research and diagnostics of infectious diseases, used already known immune serums and vaccine preparations and developed their own similar agents to combat infections that were relevant in those years: rabies, plague, cholera, typhoid fever, tuberculosis. All Russian scientists, disciples of Louis Pasteur as well as its friend and colleague I.I. Mechnikov continued to serve to a society owing to great achievements in the field of microbiology by transferring own knowledge and experience to numerous disciples continuers of work of the great scientist Louis Pasteur. Many of them were immortalized in the names of research institutes, departments and laboratories.